The Elephant in the Room – A Critical Interpretive Synthesis of Older Adults' Sexuality. Issue 1 (2nd January 2022) - Cismaru-Inescu, Adina; Adam, Stéphane; Nobels, Anne; Kempeneers, Philippe; Beaulieu, Marie; Vandeviver, Christophe; Keygnaert, Ines; Nisen, Laurent
Abstract: Objectives: This study aimed to explore past studies that have focused exclusively on the sexuality of adults older than 65 from a positive public health approach. Methods: We performed a critical interpretive synthesis, starting with the literature review on sexual behaviors in later life, adding policy documents on aging sexuality, and bringing new perspectives. Results: Older adults continue to be sexually active. Healthcare professionals lack knowledge and communication skills surrounding aging sexuality and no policies before 2013 mention aging sexuality. Conclusions: We posit that society's view of later life sexuality reflects on practice, policies, and research on this topic, which influence back society's view.